Poverty reduction and the world bank: Progress in operationalizing the WDR 2000/2001 - World Bank (Washington, D.C.: World Bank, 2002)
This report discusses how the Bank is responding to this challenge and translating the approach of the World Development Report 2000/2001 on poverty to practice
osa 5/9/16
Loans
Keywords: Poverty; Poverty - effect